The Effect of Proposed Exercises On Arms And Shoulders Strength And Forehand and Backhand Performance Speed in Lawn Tennis - Nabhan, Nada (Journal of Physical Education, 2016)
Tennis players face many conditions that require strength to win. Thus, the proposed exercises play an important role in improving explosive power, power defined by speed, and maximum speed. The importance of the research lies in using special exercises to improve strength defined by speed and its effect on the speed of performing forehand and backhand in lawn tennis. The problem of the research lies in the coaches' lack of interest in power defined by speed exercises that are very effective in improving performance speed. The aim of the research was to identify the effect of these exercises on developing the speed of arms and shoulders as well as their effect on the speed of performing forehand and backhand in physical education and sport sciences college students/ University of Baghdad. The researcher used the experimental method. The subject were (10) players divided equally into two groups, experimental and controlling. The experimental group followed the proposed training while the controlling group followed the traditional program. The researchers concluded that the training program developed strength defined by speed as well as developing the strength of arms and shoulders to perform forehand and backhand.